2005
DOI: 10.1177/1523422305277176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unexpected Leadership Changes and Budget Crisis on Change Initiatives at a Land-Grant University

Abstract: The problem and the solution. One of the greatest challenges to successful organization development is managing the impact of unexpected events on planned institutional change initiatives. Too often, in the face of crises, organizational development efforts are put on autopilot and attention is shifted away from identified objectives to the immediate problem at hand. This article examines three organizational change initiatives undertaken at a Midwestern land-grant university during the period 2000 to 2004. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Rather than establishing OD as a new, stand-alone change effort, these cases show how OD has influenced change by building on existing change initiatives. In the case discussed by Latta and Myers (2005), change is slowly evolving in a way that is careful to be consistent with the influential Report on the Future of Research and Graduate Education at UNL: A 2020 Vision and with the Gallup workplace climate initiative. Cornell's OD services have partnered with and built on several related initiatives during its decade-long history.…”
Section: Organization Development Builds On and Leverages The Work mentioning
confidence: 94%
See 1 more Smart Citation
“…Rather than establishing OD as a new, stand-alone change effort, these cases show how OD has influenced change by building on existing change initiatives. In the case discussed by Latta and Myers (2005), change is slowly evolving in a way that is careful to be consistent with the influential Report on the Future of Research and Graduate Education at UNL: A 2020 Vision and with the Gallup workplace climate initiative. Cornell's OD services have partnered with and built on several related initiatives during its decade-long history.…”
Section: Organization Development Builds On and Leverages The Work mentioning
confidence: 94%
“…Three university cases used these two different approaches to change as part of their explana-tions of how change occurs in their institutions. These are Cornell University and the university cases described by McLean (2005) and by Latta and Myers (2005). This section discusses the use of OD (Beer and Nohria's Theory O) and top management-driven change (Theory E) in these cases as part of how the authors discuss change at their institutions.…”
Section: Theories E and O Of Change And The University Casesmentioning
confidence: 99%
“…restructuring, downsizing and government funding cuts); such job-related stress can have an adverse impact on their professional work and personal welfare. Latta and Myers (2005) found that unexpected budget cuts, along with planned change and leadership turnover, led to the elimination of both tenured and non-tenured academic positions, the downsizing or elimination of academic departments and the loss of trust in fundamental tenets of academic community; these consequences of organizational change resulted in negative impacts on teaching, research and outreach missions of the university and little progress towards strengthening the academic culture. Similarly, Magner, Welker, and Campbell (1995) found that dissatisfaction with budgetary issues had a negative impact on organizational commitment in a sample of international managers.…”
Section: Introductionmentioning
confidence: 97%
“…Traditionally focused on enhancing individual skills for teaching and learning, these units are being called on to expand the scope of their services to encompass all areas of institutional mission in support of broader strategic goals (Chism, 1998;Ruben, 2005). Individual faculty development efforts are giving way to opportunities for working with intact academic units (Dwyer, 2005;Latta & Myers, 2005), targeted administrative groups such as department chairs (Austin, 1994;Yen, Lang, Denton, & Riskin, 2004), leadership development initiatives (Turnbull & Edwards, 2005), and senior planning teams (McLean, 2005;Warzynski, 2005). The intent of these efforts extends beyond attention to immediate results, to address the strategic goals of developing future leadership capacity and supporting long-term institutional objectives (Chesler, 1998;Gardiner, 2005;Patrick & Fletcher, 1998).…”
Section: New Roles For Faculty Developersmentioning
confidence: 99%